Association between KIR polymorphisms and ankylosing spondylitis in populations: A meta-analysis. Issue 6 (November 2014) - Fan, Dazhi; Liu, Si; Yang, Ting; Wu, Shanshan; Wang, Sheng; Li, Guixing; Zeng, Zhen; Duan, Zhenhua; Xia, Guo; Ye, Dongqing; Zou, Yanfeng; Xu, Shengqian; et al.
Abstract Objectives. Published association studies of killer cell immunoglobulin-like receptors (KIRs) and ankylosing spondylitis (AS) in populations are inconsistent. The aim of this study is to determine whether the KIR polymorphisms confer susceptibility to AS in populations by conducting a meta-analysis. Methods. A computer search was carried out up to August 2013 for literature pertaining to AS and KIR polymorphisms. Publications addressing the association between the KIR polymorphisms and susceptibility to AS in populations were selected from the Pubmed, Elsevier Science Direct, China National Knowledge Infrastructure (CNKI) and Chinese Biomedical Literature Database (CBM) databases. The odds ratio (OR) with 95% confidence interval (95%CI) was calculated. Results. A total of 13 case-control studies in 9 articles were included in this meta-analysis. Meta-analysis results identified two positive associations of 2DS4 and 3DS1 with susceptibility to AS in populations. In subgroup analysis, there was a positive association between 2DS4 and susceptibility to AS in Asians, but not in Caucasians. And there were associations between 3DL1, 3DS1 and susceptibility to AS in Caucasians, but not in Asians. Results of subgroup analysis also showed that there were associations between 2DL5, 2DS4, 2DS5, 3DL1, 3DS1 and susceptibility to AS in HLA-B*27-positive patients and HLA-B*27-positive healthy controls. Conclusions. This meta-analysis confirms that 2DS4 and 3DS1 might be potential risk factors for AS in populations.